Towards Improving Decision-making Capabilities in Higher Education for Stressful Periods: A Participatory Action Research Approach (PARA) - Mabade, Avhurengwi Samson (Advances in Social Sciences Research Journal, 2022)
Of late, South African higher education sectors have been engulfed with spontaneous and frequent protests by students. These protests have often led into violence and horrifying physical injuries to some victims, some victims being students, while some are members of the public. Amongst others, the latest episodes of the #FeesMustFall movement and protests bear witness. During this violence, valuable time is lost and assets are vandalized and also destroyed. The state has also suffered implacable budgetary loses when property gets torched and destroyed. Various studies have mushroomed investigating the causes of these violence and in addition their resolves. However, this literature has a gap because it fails to investigate the critical issue on decision-making during critical times. Decision-making plays a major role during these times. However, decision-making being not a simplistic issue needs to be developed to an extent of worthwhile decision-making and avoiding naïve arguments as well as opportunism. The aim of this article is to improve decision-making capabilities through knowledge management and critical thinking. Critical thinking enhances the potential of being judgmental. This qualitative study which uses desktop approach and PARA focuses on the higher education sector of South Africa. However, the higher education sector is vast as it includes hundreds of TVET colleges and several universities for example. For the purpose of this study, one rural-based university was purposively selected for study. The data was collected through qualitative technique. Collected data was analyzed using thematic code and results presented as main report